2014
DOI: 10.1136/bcr-2014-208117
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing bile duct syndrome in the context of concurrent temozolomide for glioblastoma

Abstract: Temozolomide, an oral alkylating agent, is used in the treatment of glioblastoma. We describe a case of a 62-year-old woman developing jaundice with significant derangement of liver function tests on day 17 of focal radiotherapy with concomitant temozolomide. There was no structural abnormality on imaging and liver biopsy was performed. Pathology revealed absence of small terminal bile ducts affecting up to 60% of sampled portal tracts and senescence of many of the remaining small bile ducts, in keeping with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Although DILI is an uncommon etiology for the VBDS, several medications have been reported to be related to the development of VBDS after liver injury. These medications include: antifungals or antibiotics like terbinafine, [ 12 ] meropenem, [ 13 ] and azithromycin; [ 11 ] anti-seizure medications such as valproic acid, [ 14 ] carbamazepine, [ 15 ] and lamotrigine; [ 16 ] and NSAIDs such as loxoprofen, diclofenac, and ibuprofen in pediatric cases [ 5 – 8 , 17 ]. Five cases of ibuprofen-induced liver injury with the complication of VBDS have been reported by far and all were children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DILI is an uncommon etiology for the VBDS, several medications have been reported to be related to the development of VBDS after liver injury. These medications include: antifungals or antibiotics like terbinafine, [ 12 ] meropenem, [ 13 ] and azithromycin; [ 11 ] anti-seizure medications such as valproic acid, [ 14 ] carbamazepine, [ 15 ] and lamotrigine; [ 16 ] and NSAIDs such as loxoprofen, diclofenac, and ibuprofen in pediatric cases [ 5 – 8 , 17 ]. Five cases of ibuprofen-induced liver injury with the complication of VBDS have been reported by far and all were children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient had a complete recovery within 8 months [ 6 ]. These reports suggested that ibuprofen can cause acute VBDS, and weight-based ursodeoxycholic acid was commonly used for VBDS with supportive care, although steroids, immunosuppressive agents, or plasmapheresis were provided occasionally [ 12 , 18 ]. Similar to the clinical presentations described in children, our case had acute onset of jaundice and VBDS developed approximately at weeks 4–6 from the ibuprofen-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult to assess the exact hepatotoxic role of antineoplastic agents in cancer patients, sometimes critically ill, in whom liver injury is likely to be multifactorial. However, reasonably well documented cases of DILI with bile duct injury have been reported, especially with docetaxel [24], paclitaxel (or nab-paclitaxel) [24] and temozolomide [25,26].…”
Section: Systemic Chemotherapiesmentioning
confidence: 99%
“…Anecdotal beneficial effects of ursodeoxycholic acid (UDCA) have been shown in cholangiopathy related to prochlorperazine [22], chlorpromazine [23] and temozolimide [24]. UDCA is known to stimulate biliary secretion of bile acids and other organic compounds, reduces the hydrophobic bile acid component of bile, inhibits the intrinsic apoptotic pathway and promotes cell survival in hepatocytes, through activation of the epidermal growth factor receptor (EGFR) [68].…”
Section: Therapy and Outcomementioning
confidence: 99%